1977
DOI: 10.1007/bf00496763
|View full text |Cite
|
Sign up to set email alerts
|

Collection method dependant concentrations of some metabolites in human tear fluid, with special reference to glucose in hyperglycaemic conditions

Abstract: Concentrations of the metabolites glucose, lactate, pyruvate, and urea were determined in human tear fluid. Collection of the tears in glass capillaries, without mechanical irritation, permitted the estimation of naturally occurring levels of these metabolites. Glucose concentrations were very low, also in diabetics with high blood glucose levels. Lactate was present at higher levels and pyruvate and urea in about the same concentrations as normally for blood. Collection of the tears with filter paper strips a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 15 publications
4
41
0
Order By: Relevance
“…However, the findings for LF glucose in this study are consistent with those in diabetic dogs, where LF glucose concentrations were higher than the LF glucose levels in normal dogs . The strong correlation between the LF and plasma urea nitrogen concentrations were seen in the cats of our study is consistent with the results in humans, dogs, and horses . This finding leads us to conclude that the biochemical analysis of LF has clinical utility for the diagnosis of an increased BUN in humans, horses, dogs, and cats.…”
Section: Discussionsupporting
confidence: 90%
“…However, the findings for LF glucose in this study are consistent with those in diabetic dogs, where LF glucose concentrations were higher than the LF glucose levels in normal dogs . The strong correlation between the LF and plasma urea nitrogen concentrations were seen in the cats of our study is consistent with the results in humans, dogs, and horses . This finding leads us to conclude that the biochemical analysis of LF has clinical utility for the diagnosis of an increased BUN in humans, horses, dogs, and cats.…”
Section: Discussionsupporting
confidence: 90%
“…T h e mechanical response does agree with observations made by earlier investigators, when comparing tear sample concentrations collected by capillary versus filter paper strips (van Haeringen & Glasius 1977). The latter, through surface irritation, generally resulted in a several fold increase in glucose concentration as compared to those collected by smooth glass capillary.…”
Section: Discussionsupporting
confidence: 90%
“…The tear glucose concentration from this subject during the two sessions ranged from 13 to 51°M°with°an°average°of°32°M°(Table°1).°The concentration of tear glucose determined in this work for this nondiabetic subject is about 4-fold less than the tear°glucose°concentrations°recently°reported° [8]. Whereas previous studies used collection methods that either°touched°the°eye°or°chemically°stimulated°tears° [7,9,°10],°we°used°glass°micro-capillaries°to°collect°a°single microliter volume of tear fluid from the tear meniscus without touching the eye. This decrease in reported tear glucose concentration is likely due to our less irritating method of tear collection.…”
Section: Resultsmentioning
confidence: 81%
“…They used a glucose dehydrogenase method to analyze chemically stimulated tears collected with a capillary and mechanically stimulated tear fluid collected by filter paper. Van Haeringen and Glasius found higher glucose concentrations in the tear fluid collected by filter paper and concluded that the increase is due to the mechanical stimulation of the corneal and conjunctival epithelium [9]. Other studies reported similar findings in experiments on rabbits [10] and in subjects who were tested immediately after swimming [7].…”
mentioning
confidence: 59%
See 1 more Smart Citation